Entrepreneurial skills in the context of sports entrepreneurship education - Marnoto, Sandra (2022)
Entrepreneurship education has been widely studied in the last decades due to its documented importance for the development of a national entrepreneurial culture which in turn fosters an entrepreneurial attitude in individuals. This collective mind-set leads not only to an increase in the creation of businesses but also to more skilled professionals who are prepared to face the needs of the 21st century labour market. This change in the cultural mind-set is therefore believed to have a positive effect in terms of economic growth, GIP and employment. Although the significance of Entrepreneurship education is well stablished, the debate over the best methodologies, curricula and philosophy is not yet closed with academics and policy makers still searching for better solutions. Nonetheless, there seems to be an agreement between the participants in this debate that potential entrepreneurs must develop a set of skills that includes managerial capabilities such as marketing, finance and human resources management and soft skills like perseverance and risk taking. However, some scholars argue that more research is needed in order to identify less known entrepreneurial skills, including those required by social or sports entrepreneurship. By performing an exploratory survey among stablished sports entrepreneurs, this work aims to identify the most important skills that might be developed by future professionals in this area. The results will hopefully be important for the development of entrepreneurship teaching programs aiming social entrepreneurs in the sports activity as well as sports management curricula.